Two Different Meningioma Variants in the Same Tumor: A Rare Histopathological Finding - Reham Khubrani; Sadeq Al-Dandan (Case Reports in Pathology)
We report a case of meningioma with both secretory and lipomatous features in an advanced middle aged female patient with a 3-month history of headaches and convulsions. Radiological findings are revised and compared to other reported cases in the literature.